2004
DOI: 10.1007/bf03346273
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D status on the severity of bone disease and on the other features of primary hyperparathyroidism (pHPT) in a vitamin D deficient region

Abstract: A clear relationship between vitamin D status and the clinical indices of primary hyperparathyroidism (pHPT) severity has not been convincingly established. We proposed that such a relationship might exist, in so far as vitamin D deficiency could contribute to the severity of metabolic bone disease and promote the growth of the parathyroid tumor. Accordingly, we undertook a retrospective study and analyzed the clinical, biochemical, radiological and histopathological findings in a group of 49 patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 19 publications
4
38
2
2
Order By: Relevance
“…Bone density in a large population of postmenopausal women with osteoporosis correlated inversely with vitamin D levels 24. It has also been shown that lower vitamin D levels may contribute to the frequently encountered, severe bone manifestations, seen with primary hyperparathyroidism in Saudi Arabia and other countries with widespread vitamin D deficiency 25. Vitamin D deficiency should therefore be suspected and adequately treated in all patients with osteopenia and osteoporosis in our region.…”
Section: The Role Of Vitamin D Deficiencymentioning
confidence: 88%
“…Bone density in a large population of postmenopausal women with osteoporosis correlated inversely with vitamin D levels 24. It has also been shown that lower vitamin D levels may contribute to the frequently encountered, severe bone manifestations, seen with primary hyperparathyroidism in Saudi Arabia and other countries with widespread vitamin D deficiency 25. Vitamin D deficiency should therefore be suspected and adequately treated in all patients with osteopenia and osteoporosis in our region.…”
Section: The Role Of Vitamin D Deficiencymentioning
confidence: 88%
“…It has been suggested that preoperative serum alkaline phosphatase concentrations may predict the degree and duration of hypocalcaemia after successful parathyroidectomy (46). Other risk factors for the development of HBS include evidence of bone disease, such as osteitis fibrosa cystica, subperiostal bone erosions or bone cysts (4,15,16,17,26,27,31,39) and the volume and weight of the removed hyperactive parathyroid gland(s) (1, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Radiological bone disease before surgery Radiological evidence of PHPT-related bone disease has been reported to be an important risk factor for the development of HBS (4,16,17,26,27,31,39). Fourteen of 18 case reports on HBS indeed report skeletal abnormalities, such as subperiostal erosions, lytic lesions, brown tumours and multiple fractures …”
Section: Risk Factors For the Development Of Hbsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological mechanisms responsible for the low serum 25(OH)D level in PHPT are not completely clarified. The data obtained from several studies suggest that vitamin D status might influence the clinical and biological expression of PHTP [1,2,[4][5][6][7][8][9][10][11][12][13][14][15] and even recovery after surgical treatment [11,16,17], although some authors have not found such an association [18,19].…”
Section: Introductionmentioning
confidence: 99%